Ensino por múltiplos exemplares e a emergência de nomeação bidirecional e incidental em crianças autistas - CARDUNER, Bernardo Serruya (Universidade Federal do Pará, 2025)
Bidirectional naming (BN) is a behavioral repertoire characterized by the emergence of listener responses to objects/events after teaching speaker responses to those objects/events, and vice versa. The consolidation of this repertoire as a generalized behavioral relation leads to incidental bidirectional naming (IBN) — the emergence of both speaker and listener responses to objects/events after exposure to their names — which is considered a pivotal repertoire for language development. The multiple exemplar instruction (MEI) is a procedure that has been pointed out as capable of inducing IBN in autistic individuals. This study aimed to evaluate the effect of MEI with rotation of listener (auditory-visual match-to-sample-AVMTS) and speaker (intraverbal tact) trials, without echoic requirement, in inducing BN and IBN in two autistic children. Participants could be exposed to up to five experimental stages, depending on their performance: 1) BN and IBN pre-tests; 2) MEI; 3) BN and IBN post-tests; 4) BN and IBN generalization tests; and 5) BN and IBN maintenance tests. Results showed that MEI did not result in the emergence of BN and IBN, with participants displaying unidirectional listener naming since the pre-tests. Methodological aspects to be evaluated in future studies on the role of MEI in the induction of BN and IBN are discussed, including the effects of requiring or blocking echoics during MEI, establishing the reinforcing function of the social consequences used in teaching AVMTS and intraverbal tact, and the reinforcing function of observation responses to stimuli.